2015
DOI: 10.1590/1677-5449.20140049
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diabetic foot amputations

Abstract: Background: Diabetes and the problem of the diabetic foot specifically are a severe burden on the public healthcare system. Amputations caused by this condition are still common in our setting (Brazil), although the true magnitude of the problem is not known with certainty. Lower limb amputation rates have come to be seen as an indicator of the quality of preventative care of the diabetic foot. Objective: To identify associations between amputations and factors related to people, to morbidities and to primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
21

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 14 publications
(29 reference statements)
1
19
0
21
Order By: Relevance
“…The decrease of QOL due to high blood glucose in patients with diabetic foot ulcer might because high blood glucose will cause the wound to deteriorate into more severe foot ulcer. A previous study by Santos, Carvalho, Souza, & Albuquerque (2015) showed that high blood glucose would cause deterioration of wound to a more severe ulcer, and finally lead to foot amputation.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of QOL due to high blood glucose in patients with diabetic foot ulcer might because high blood glucose will cause the wound to deteriorate into more severe foot ulcer. A previous study by Santos, Carvalho, Souza, & Albuquerque (2015) showed that high blood glucose would cause deterioration of wound to a more severe ulcer, and finally lead to foot amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations indicate that inadequate management of blood glucose level is a factor associated with the presence of feet ulcers (28) and with amputation among individuals with diabetic foot (29) . However, it is important to analyze the influence of educational interventions on outcomes associated with complications of DM, in addition to the specific serum levels of glucose or glycated hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory loss secondary to peripheral diabetic neuropathy, at times, goes unnoticed by the patient and the first presentation can be feet ulcer (32) . In Brazil, the rate of amputations among individuals with diabetic foot reaches 58.2% (29,37) . In addition to inadequate control of blood glucose, other factors associated with amputation include: lack of feet examination during the most recent medical consultation, lack of instructions on the care of feet in the consultations held the previous year, and non-adherence to pharmacological treatment according to medical advice (29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of foot ulcers reaches 4-10% of those with the disease. The absence of treatment or inadequacy of the same causes serious consequences, including amputation and death (Powers, Higham, Broussard, & Phillips, 2016;Santos, Sobreira, Nunes, & Morais, 2013;Wang et al, 2016). In young patients, the treatment method consists of aggressive revascularization and infection control to avoid amputations.…”
Section: Introductionmentioning
confidence: 99%